2023
DOI: 10.4103/ijo.ijo_3209_22
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes of early enhancement following small incision lenticule extraction versus laser in situ keratomileusis

Abstract: Purpose: To compare visual outcomes of early enhancement following small incision lenticule extraction (SMILE) versus laser in situ keratomileusis (LASIK). Methods: Retrospective analysis of eyes (patients operated in the setting of a tertiary eye care hospital between 2014 and 2020) requiring early enhancement (within one year of primary surgery) was conducted. Stability of refractive error, corneal tomography, and anterior segment Optical Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The visual outcomes of SMILE generally parallel those of LASIK, characterized by exceptional postoperative visual acuity and refractive outcomes [19][20][21]. A comparative study between SMILE and LASIK revealed that approximately 90%-95% of patients achieved uncorrected distance visual acuity of 20/20 within the initial day following SMILE surgery [21].…”
Section: Visual Outcomesmentioning
confidence: 99%
“…The visual outcomes of SMILE generally parallel those of LASIK, characterized by exceptional postoperative visual acuity and refractive outcomes [19][20][21]. A comparative study between SMILE and LASIK revealed that approximately 90%-95% of patients achieved uncorrected distance visual acuity of 20/20 within the initial day following SMILE surgery [21].…”
Section: Visual Outcomesmentioning
confidence: 99%